Single-period newsvendor modelling of flu vaccination order quantities. Issue 4 (2015) - Scott, Rebecca A.; Nowicki, David R.; Prybutok, Victor R.
The objective of this paper is to determine optimal inventory levels of flu vaccines at one medical facility using the newsvendor model while also maintaining customer service levels and maximising profit. Using four years of empirical evidence, we illustrate the optimal ordering quantity of flu vaccine by healthcare managers to provide proper medical coverage. This research provides an initial step for ordering quantities of perishable biopharmaceuticals. The research also develops a framework for the logistics of ordering in the presence of multiple constraints throughout the supply chain network. An important contribution of this work is demonstrating the value of the posited logistics model within the context of a healthcare application that has the potential to influence practice.